IMPACT-Global Hip Fracture Audit: Nosocomial infection, risk prediction and prognostication, minimum reporting standards and global collaborative audit: Lessons from an international multicentre study of 7, 090 patients conducted in 14 nations during the COVID-19 pandemic. Issue 6 (December 2022) - Hall, Andrew J.; Clement, Nicholas D.; Ojeda-Thies, Cristina; MacLullich, Alasdair MJ.; Toro, Giuseppe; Johansen, Antony; White, Tim O.; Duckworth, Andrew D.; ,; Abdul-Jabar, Hani; Abu-Rajab, Rashid; Abugarja, Ahmed; et al.
Abstract: Aims: This international study aimed to assess: 1) the prevalence of preoperative and postoperative COVID-19 among patients with hip fracture, 2) the effect on 30-day mortality, and 3) clinical factors associated with the infection and with mortality in COVID-19-positive patients. Methods: A multicentre collaboration among 112 centres in 14 countries collected data on all patients presenting with a hip fracture between 1st March-31st May 2020. Demographics, residence, place of injury, presentation blood tests, Nottingham Hip Fracture Score, time to surgery, management, ASA grade, length of stay, COVID-19 and 30-day mortality status were recorded. Results: A total of 7090 patients were included, with a mean age of 82.2 (range 50–104) years and 4959 (69.9%) being female. Of 651 (9.2%) patients diagnosed with COVID-19, 225 (34.6%) were positive at presentation and 426 (65.4%) were positive postoperatively. Positive COVID-19 status was independently associated with male sex (odds ratio (OR) 1.38, p = 0.001), residential care (OR 2.15, p < 0.001), inpatient fall (OR 2.23, p = 0.003), cancer (OR 0.63, p = 0.009), ASA grades 4 (OR 1.59, p = 0.008) or 5 (OR 8.28, p < 0.001), and longer admission (OR 1.06 for each increasing day, p < 0.001). Patients with COVID-19 at any time had a significantly lower chance of 30-day survival versus those without COVID-19 (72.7% versus 92.6%, p < 0.001). COVID-19 was independently associated with an increased 30-day mortality risk (hazard ratio (HR) 2.83, p < 0.001). Increasing age (HR 1.03, p = 0.028), male sex (HR 2.35, p < 0.001), renal disease (HR 1.53, p = 0.017), and pulmonary disease (HR 1.45, p = 0.039) were independently associated with a higher 30-day mortality risk in patients with COVID-19 when adjusting for confounders. Conclusion: The prevalence of COVID-19 in hip fracture patients during the first wave of the pandemic was 9%, and was independently associated with a three-fold increased 30-day mortality risk. Among COVID-19-positive patients, those who were older, male, with renal or pulmonary disease had a significantly higher 30-day mortality risk. Highlights: IMPACT-Global is the largest multicentre observational study undertaken solely in T&O Prevalence of COVID-19 in hip fracture patients was ten times higher than background COVID-19 was independently associated with a 3x increased 30-day mortality risk Nosocomial transmission likely had significant role in COVID-19 prevalence & mortality Lessons applicable to audit and practice in future communicable disease outbreaks